2002
DOI: 10.1080/10473289.2002.10470856
|View full text |Cite
|
Sign up to set email alerts
|

The Catalytic Incineration of Styrene over an Mn2O3/Fe2O3 Catalyst

Abstract: In this study, styrene monomer (SM) was treated by a commercial catalyst, Mn 2 O 3 /Fe 2 O 3 , in a fixed-bed reactor. The study can be classified into two major parts. First, the effects of operating factors, such as temperature, SM concentration, space velocity, and O 2 concentration, on the performance of the catalyst were investigated. Second, two catalyst life tests were carried out to characterize the deactivation effect of SM.The results show that the catalyst results in higher conversion of SM at a hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…This is inconsistent with the results of Lou and Lee [34], which showed that the effect of the O 2 content (%) on the reaction rate was insignificant in the process of catalytic incineration of CHCl 3 . A detailed review of the work in the literature on the effect of O 2 concentration for the catalytic decomposition has been presented by Chu et al [35], Tseng and Chu [36], and Tseng et al [22]. They indicated that the O 2 concentration had a positive effect on the conversion of ethyl mercaptan and methyl isobutyl ketone, respectively.…”
Section: Resultsmentioning
confidence: 94%
“…This is inconsistent with the results of Lou and Lee [34], which showed that the effect of the O 2 content (%) on the reaction rate was insignificant in the process of catalytic incineration of CHCl 3 . A detailed review of the work in the literature on the effect of O 2 concentration for the catalytic decomposition has been presented by Chu et al [35], Tseng and Chu [36], and Tseng et al [22]. They indicated that the O 2 concentration had a positive effect on the conversion of ethyl mercaptan and methyl isobutyl ketone, respectively.…”
Section: Resultsmentioning
confidence: 94%
“…Although very active, the application of catalyst is using to low operating temperatures because of volatile formation and toxic chromium oxy-chloride. [1].This study we also notice that function of the oxy-dechlorination of 1, 2-dichloroethane with excessive oxygen was carried out during laboratory scale tubular reactor with packed Pt and Fe 2 O 3 catalyst. Spivey [3] indicated that those major parameters affecting catalytic incineration of VOCs included catalyst type, VOC speciation, VOCs concentration, operating temperature, space velocity and O 2 concentration.…”
mentioning
confidence: 96%
“…Treatment of environmental pollution caused by Cl-VOC (e.g. dichloromethane, 1,2-dichloroethane) emissions has become an important topic recently [1]. Methods usually used to abate VOCs include incineration with or without catalyst, adsorption, absorption, and condensation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Volatile organic compounds (VOCs) are organic compounds such as aliphatic hydrocarbons, aromatic hydrocarbons, esters, ethers, and halohydrocarbons that have a high vapor pressure under normal room-temperature conditions (Harper, 2000;Li et al, 2009;Tseng et al, 2001). Sources of VOC emissions include fuel combustion, transport, industrial processes, solvent use, and storage and distribution of fuels (Chang et al, 2002;Li, 1996).…”
Section: Introductionmentioning
confidence: 99%